2022
DOI: 10.1108/srj-04-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate social responsibility yield financial returns in Islamic banking?

Abstract: Purpose This study aims to examine whether corporate social responsibility (CSR) of Islamic banking is delivering financial returns or otherwise enhancing the cost. Design/methodology/approach The methodology of this study includes the content-analysis approach with aid of the CSR disclosure index, and it deploys the partial least squares regression to examine the CSR-financial performance relationship. Regarding CSR disclosure and financial measures, this study takes the data from the annual reports of Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 123 publications
1
13
2
Order By: Relevance
“…Accounting information in the report on economic activities is described as the information used for the decision-making of the internal and external stakeholders of a company (Alam, 2022). Companies must consider social activities as an investment for the future (Zafar et al, 2022). Prioritizing the strength of the community as a stakeholder shows the company's efforts in sustainability (Dosinta & Astarani, 2021).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Accounting information in the report on economic activities is described as the information used for the decision-making of the internal and external stakeholders of a company (Alam, 2022). Companies must consider social activities as an investment for the future (Zafar et al, 2022). Prioritizing the strength of the community as a stakeholder shows the company's efforts in sustainability (Dosinta & Astarani, 2021).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Many studies support the use of CSR as an indicator of a firm's financial health (Zafar, Sulaiman, & Nawaz, 2022). Financially healthy firms are more likely to get engaged into the CSR activities (Kuzey, et.al., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only Rossi et al (2021) has found a moderating effect of social and ethical practices on the positive relationship between environmental disclosure and the firm's financial performance. While most of the literature uses regression analysis, we propose to use Partial Least Squares as a methodology, following Pajuelo‐Moreno and Duarte‐Atoche (2019), Gallardo‐Vázquez and Juárez (2022), and Zafar et al (2022).…”
Section: Introductionmentioning
confidence: 99%